Lessons and challenges of practice of traditional medicines as an alternative for COVID-19 vaccine in Tanzania - Paul E. Kazyoba; Chima E. Onuekwe; Alexander Makulilo; Tumaini Haonga; William Mwengee; Grace Saguti (Journal of Public Health in Africa, 2025)
Background: The COVID-19 pandemic brought a peculiar experience across the world as populations were engulfed in shocks and panic because of lack of substantive interventions during its early days. Different intervention options were tested, including traditional medicines. Despite the lack of scientific evidence on safety and efficacy, traditional medicines brought calmness and dispelled fear associated with the disease in Tanzania. On the other hand, the introduction of COVID-19 vaccines was met by hesitancy, rumours and doubts about its safety and efficacy.